Effects of health education program on self-breast examination on the level of competency among women - Frio, Marilyn Medez-
Breast cancer incidence and mortality has progressed over the years. Promotion of self-breast examination (SBE) as a secondary preventive measure has been done. Health education program (HEP) on self-breast examinations aims to educate women on the importance of a regular monthly practice and acquiring competency on SBE for early detection of breast lumps.This study investigated the effects of health education program on self-breast examination on the level of competency among women. Specifically, it aimed to determine the level of knowledge, skills, and degree of attitude on SBE before and after the health education program. It also determine the significant relationship of specific personal and enabling factors to the level of competency on SBE. The health education program on SBE included lecture, video viewing of SBE, provision of a vernacular (Ilonggo) one-page illustrated hand-out of steps on SBE and return demonstration.The study was conducted in a community and included forty eight (48) women as participants. A non-experimental before and after design was used. Tools were constructed to measure the baseline and outcome of the dependent variables. Level of knowledge, and degree of attitude were ascertained by a written test while level of skills was assessed using a rating scale while the participant demonstrated SBE. Participants answered a questionnaire to establish the personal and enabling factors.Percentage computation determined the profile of the participants. Mean scores were computed for the level of competency and t-test for dependent samples was employed to determine the significant difference before and after the health education program. Significant relationship of the health education program to the level of competency on SBE was measured using Pearson r. Level of significance was set at .05.The study revealed that:1. there is a significant difference in the level of knowledge of women about SBE before and after the HEP (t=0.616).2. there is a significance difference in the level of skills of women in performing SBE before and after the HEP (t = 0.187).3. there is a significant difference in the degree of attitude of women in performing SBE before and after the HEP (t = 0.538).4. the following factors have significant and negative relationship between level of competency on SBE:a. age (r = -0.4609)b. educational level (r = -0.4530)No significant relationship between level of competency on SBE was found among the following factors:a. civil statusb. family history of cancerc. value placed on breastd. motivation to perform SBEe. social support5. there is a significant difference in the level of competency of women on SBE before and after the HEP (t = 0.803).Competency on SBE was acquired through the health education program. HEP on SBE was easily comprehended, and appreciated by women whether young or old, regardless of their level of education. The significant difference in the level of competency before and after the health education program confirmed that knowledge about SBE could be advanced, skills to perform SBE be acquired, and attitude to perform SBE be improved. SBE requires very minimal effort on the part of the woman, yet perceiving the benefits would most likely encourage her to practice SBE regularly. In same manner, HEP on SBE does not entail so much time and thus could be integrated in client care by nurses in their respective field.